THE STRUCTURE OF SCIENTIFIC REVOLUTION: A BRIEF EXPLANATION - Alves, Marcos Antonio [UNESP]; Valente, Alan Rafael [UNESP] (Univ Fed Reconcavo Bahia, Centro Formacao Professores, 2020)
How is scientific progress effected? Are there criteria for choosing scientific theories? What is the impact of cognitive and extracognitive values on such choices? To address issues like these, science philosopher Thomas Kuhn develops a structuralist perspective with a historical basis. In this paper, we expose the structure of scientific revolutions suggested by this thinker. Initially, we deal with the notion of paradigm, a key concept in its explanation of the functioning of science and scientific progress. Then we present the phases through which an area of research commonly goes through its trajectory: pre-science, normal science, crisis and revolution. We conclude the paper by drawing some parallels of this thinker's position with other epistemological perspectives of the last century, such as Logical Positivism, Falsificationism, and Lakatos Structuralism.
Keywords: Paradigm; Scientific progress; Scientific revolution; Normal science